THE IMPACT OF HYBRID TRAINING MODELS ON SENIOR VOLUNTEERS' SERVICE EFFECTIVENESS IN NPOs - Chih-Yi Tan, (PEOPLE: International Journal of Social Sciences, 2026)
This study investigated the collaboration gap between senior home‑visiting volunteers’ experience‑oriented practices and social workers’ professional orientation within nonprofit organizations (NPOs). While volunteers play a crucial frontline role, many NPOs face challenges such as volunteer aging and reliance on long‑standing experiential rules, leading to divergent interpretations of case assessment and ethical boundaries. Existing training systems focus primarily on newcomers, leaving the retraining needs of senior volunteers insufficiently addressed. Using a qualitative case study of the T Foundation, this study drew on in‑depth interviews with senior volunteers and professional social workers to explore the dynamics underlying collaboration and conflict. Findings showed that volunteers’ experiential knowledge is vital for building community trust, yet collaboration barriers stem not from the superiority of experience or professionalism, but from the absence of mechanisms for knowledge translation and capability integration. Without a shared professional language, volunteers’ visits were often viewed as emotion‑driven material support, while social workers’ interventions were perceived as impersonal procedures. This study recommends that NPOs move beyond top‑down training and adopt blended, empowerment‑based approaches that foster mutual understanding. Strategies include action learning and case‑based workshops to transform tacit experience into organizational knowledge, two‑way mentorship to facilitate reciprocal learning, and micro‑learning modules tailored to elderly volunteers. Such mechanisms can integrate experiential and professional knowledge, creating collaborative value for organizations, volunteers, and service users.